Tinjauan Yuridis Pasal 54 UU Narkotika: Rehabilitasi Sebagai Solusi Bagi Pecandu dan Korban Penyalahgunaan Narkotika - Muhammad Hairul; Desi Anisah (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The Article 54 of Law Number 35 of 2009 concerning Narcotics, Drug Rehabilitation is a repressive action carried out for Addicts and Victims of Narcotics Abuse. This rehabilitation is the restoration to the previous (original) position and the improvement of individuals, hospital patients or disaster victims so that they become useful human beings and can live in society. Rehabilitation actions are aimed at victims of drug abuse to restore or develop the physical, mental, and social abilities of the sufferer concerned. In addition to recovery, rehabilitation is also a treatment or treatment for drug addicts, so that they can recover from their addiction to narcotics. This research is focused on two problem formulations, namely how the legal status of rehab for addicts according to Law Number 35 of 2009. What are the steps of the Government's intervention in efforts to protect Drug Addicts. This research is normative research, which is descriptive analytical and sources of legal materials through primary, secondary, and tertiary legal materials. Legal data collection techniques through document studies (literature studies), such as books, papers, articles, journals, newspapers or works from experts. From the results of this study, the provision of rehabilitation is one of the main objectives in Law Number 35 of 2009 concerning Narcotics. Where Narcotics Addicts can be classified into 2 types, namely people who use Narcotics in a state of physical or psychological dependence and people who abuse Narcotics in a state of physical and psychological dependence.